Seed rain and establishment in successional forests in Chiapas, Mexico - Carrillo Arreola, Fernando; Quintana-Ascencio, Pedro Francisco; Ramírez-Marcial, Neptalí; González-Espinosa, Mario (Instituto de Ecología, A.C., 2020)
Background and Aims: Agriculture in the tropics is decreasing, fragmenting and altering forests and forest landscapes. We hypothesized differences in species richness and dominance of life forms in the seed rain and in richness and survival in the recruit assemblages among mature forests, mid-successional forests, early successional forests, pastures and milpa fields (arable lands with maize) surrounded by natural and human disturbed habitats. Methods: Samples of seeds and plants were collected during a year in Lacanjá-Chansayab and Bonampak-Bethel, in the buffer zone of the Montes Azules Biosphere Reserve, Selva Lacandona, Chiapas, Mexico. We deployed 14 seed traps in 12 sites representing a gradient of vegetation succession (2 sites × 6 habitats × 14 traps; n = 168 traps). Independently, to assess changes in recruitment and early survival, we established 15 quadrats (0.5 × 2.0 m) in each of the studied forests (2 sites × 3 habitats × 15 quadrats; n = 90 quadrats). Key results: We collected ~13,600 seeds of 144 species from 48 botanical families. Mature forests had the highest seed rain species richness (60-61) and pastures (14-11) the lowest. We observed a decline in species richness and a change in dominance of life forms in the seed rain from less disturbed to most perturbed habitats. Mature forests included seeds of diverse tree species while the assemblage in pastures was dominated by seeds of few grass species. Intensive traditional milpa fields showed homogeneous seed assemblages. For the new recruits, we recorded ~3,416 individuals (<0.5 m height) of 238 morphospecies in 42 families, 129 were identified to species level. The largest number of species occurred in mature and mid-successional stands compared to early forests. Annual survival of recruits was higher in mid- and late successional forests than in early ones.Conclusions: We document species loss and widespread simplification and homogenization in community composition due to pervasive effect of humans on remnant tropical lowland forests.